Factors Associated With Contact Dermatitis Symptoms Among Scavengers At Talang Gulo Landfill, Jambi City, 2021 - Sholeha, Maratus; Ena Sari, Rumita; Hidayati, Fajrina (LPPM Universitas Jambi, 2025)
Background: Occupational skin diseases account for approximately 80% of contact dermatitis cases. Contact dermatitis can occur in various types of occupations, including scavenging. A preliminary study conducted at the Talang Gulo Landfill, Jambi City, in 2020 found that 7 out of 10 scavengers experienced symptoms of contact dermatitis. This study aimed to determine factors associated with contact dermatitis symptoms among scavengers at the Talang Gulo Landfill, Jambi City. Method: This was an analytic observational study using a cross-sectional design. A total of 62 respondents were recruited using accidental sampling. Data were analyzed using univariate analysis and the chi-square test (95% CI; p-value = 0.05). Result: The univariate analysis showed that 67.7% of scavengers reported symptoms of contact dermatitis. Bivariate analysis using the chi-square test showed significant associations between contact dermatitis symptoms and age (p-value = 0.019), gender (p-value = 0.000), personal hygiene (p-value = 0.000), use of personal protective equipment (PPE) (p-value = 0.015), duration of contact (p-value = 0.000), and frequency of contact (p-value = 0.010). Meanwhile, no significant associations were found for years of service (p-value = 0.083) and education level (p-value = 0.515). Conclusion: In conclusion, age, gender, personal hygiene, PPE use, duration of contact, and frequency of contact were significantly associated with contact dermatitis symptoms among scavengers at the Talang Gulo Landfill, Jambi City, whereas years of service and education level were not..